Mathematical simulation of chlorophyll a fluorescence rise measured with 3-(3',4'-dichlorophenyl)-1,1-dimethylurea-treated barley leaves at room and high temperatures - Lazár, D; Pospísil, P (European biophysics journal, 1999)
Chlorophyll a fluorescence induction (FI) measured by Plant Efficiency Analyser fluorometer at room temperature shows a typical O-J-I-P pattern which is at high temperature changed to an O-K-P pattern with a new step K. It has been suggested that the appearance of the K step reflects inhibition of an oxygen evolving complex (OEC). When FI is measured at room temperature with the photosystem II (PSII) herbicide 3-(3',4'-dichlorophenyl)-1,1-dimethylurea (DCMU), which blocks electron transport from Q(A) to Q(B) (the first and the second quinone electron acceptors in PSII, respectively), the time course of the FI shows a sigmoidal increase to the maximal fluorescence which is reached at a little longer time than that of the J step. Similarly, the FI measured at high temperature with DCMU reaches the maximal value of fluorescence at the time which is a little longer than that of the K step. On the other hand, the reversible radical pair model (RRP) describes energy utilization and electron transport up to Q(A). In this work we present the first, to our knowledge, RRP model extended by a description of the function of the donor side of PSII. Assuming the inhibition of the OEC or its full function, the extended RRP model successfully simulates the fluorescence rise measured with DCMU at high and room temperatures, respectively. The roles of the initial state of the OEC and the values of the rate constants in the extended RRP on the simulations of the fluorescence rise at room and high temperatures are also discussed.
Keywords: Computer Simulation; chlorofyl; Models, Chemical; Hot Temperature; Temperature; Time Factors; počítačová simulace; kyslík; Oxygen; herbicidy; časové faktory; fluorescence; Free Radicals; Models, Biological; Chlorophyll A; biologické modely; ječmen (rod); Hordeum; chemické modely; Fluorescence; Herbicides; vysoká teplota; volné radikály; diuron; Diuron; chlorofyl a; Chlorophyll; teplota